HUMANISASI PESERTA DIDIK: MEMPERTIMBANGKAN KEMBALI KONSEPSI AL-QUR’AN TENTANG MANUSIA - Amrizal Amrizal (An-Nida', 2012)
Man in education occupies the central position, because the man, biside, is seen as a educational subject, he was aeducational objects. For human subjects, he determine the pattern and direction of education, while as an onject, human become the focus of attention of all educational activities. Therefore, the Islamic educational institutions have to make operational the concept on man as the fondation of education. In order to humanition of students, the educational praxis must consider: first, the students as being composed on the body and soul; second, as individuals and social beings; third, as being free, and the fourth, as a historical creature